CORRELATION BETWEEN EXCLUSIVE BREASTFEEDING IN GROUP OF EARLY INITIATION OF BREASTFEEDING ON THE DURATION OF LACTATIONAL AMENORRHEA - Febrianto, Edison; Prabantoro, Benedictus TR; Pangemanan, Lisa (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Based on data from "Survei Demografi dan Kesehatan Indonesia" (SDKI) in2012, about four percent of births occurred 18 months apart, and six percent were less thantwo years apart, about 75 percent occurred at least three years apart. WHO’s recommendation for birth spacing is at least 24 months. A gestation interval of fewer than six months can increase maternal mortality due to premature rupture of the amniotic sac, anemia, and puerperal endometritis. The Lactational Amenorrhea Method is a natural and easy method of contraception. The LAM method is one of the contraceptive methods with a success rate of 98 percent. One of the importance of contraception, such as LAM, is to adjust the optimal birth spacing. Purpose: This study aims to determine the correlation between exclusive breastfeeding in agroup of early initiation of breastfeeding on the duration of lactational amenorrhea. Method: This study is an observational analytic study with a retrospective cohort studydesign. A simple random sampling technique is used for the sampling method. The collectionof data on the history of breastfeeding and the duration of amenorrhea was collected from the main research results by doing interviews with respondents. Results: The results of statistical tests with Spearman correlation showed that the P-valueobtained is 0.005. This value is less than p (0.05), which means a significant correlationbetween exclusive breastfeeding and the duration of lactational amenorrhea. Conclusion: There is a significant correlation between exclusive breastfeeding in the earlyinitiation of the breastfeeding group and the duration of lactation amenorrhea.